Non-local approach to free vibrations and buckling problems for cylindrical nano-structures. (15th October 2020) - Muc, Aleksander
Abstract: Non-local higher order free vibration and buckling analysis of a cylindrical nano-shell is studied in this paper based on non-local 3D elasticity theory and third order shear deformation theory proposed by Prof. J.N. Reddy. One can conclude that combination of important theories such as Reddy's shear deformation theory and non-local Tiersten-Mindlin's theory to a more complicated structure such as cylindrical nano-structures results in an important and novel work in context of structural mechanics. The governing equations of non-local elastic bending are reduced to one linear homogeneous differential equation for simply-supported boundary conditions. In the strain or stress non-local problems different physical formulations have different effects on the searched values, understood in the sense of weakening or enhancement the buckling/vibration results in comparison with the classical global approach.